PENGARUH PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KETERAMPILAN PROSES SAINS SISWA SMP - Halil Taib; Ade Haerullah; Chumidach Roini (EDUKASI, 2020)
This research aims to find out the effect of Guided Inquiry Learning Model on students' Science Process Skills. This research is Experimental research designed. The study was conducted at junior high school one West Halmahera which is a state school. The research sample consisted of Class VIIA as Experiment Class and Class VIIC as Control Class. There are 32 students in each class. The research instrument used was a questionnaire for the product expert validation test. The Science Process Skill Test with inferential analysis uses the ANACOVA test to test the research hypothesis. The results of the study showed that the science process skills of students in the pre-test had a significant value (p) of 0,000 while for the guided inquiry model of 0.010. The test results in Table 1 also obtained a significance value (sig) of 0,000. This significant value is smaller than the alpha value of 0.05, so the statistical hypothesis (Ho) is rejected and accepts the research hypothesis. Thus, it can be concluded that there is a significant influence of guided inquiry learning models on the science process skills of students of junior high school one West Halmahera.